Peningkatan Kualitas Produksi pada Usaha Kecil dan Menengah: Studi Kasus Six Sigma DMAIC pada Industri Manufaktur Peralatan Medis - Aep Saepuloh; Aswan Munang; Ade Yanyan Ramdhani; Khikmatul Aliyah; Dedi Sadudin Tjaptajani (Jurnal Kalibrasi, 2026)
Defective products are a significant issue in the production process because they lead to increased working time and operational costs. This study aims to analyze the main causes of defects in 1 m³ oxygen trolley products at CV XYZ and to formulate improvement proposals to reduce the product defect rate. The Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach was systematically applied. In the Analyze stage, the main factors causing defects included the use of paint materials that did not meet standards, lack of worker accuracy, suboptimal working environment conditions, inconsistencies in the production process, and problems related to machines and equipment. The proposed improvements included the use of standardized epoxy powder coating paint, the implementation of a 5R culture to improve workplace organization and efficiency, and the application of a check-and-balance system at every stage of the painting process. The implementation of these improvements resulted in a reduction of the dominant defect percentage from 61 percent to 40 percent. In the Control stage, analysis using a P-Chart showed that the defect proportion remained within control limits and tended to decrease. The increase in the Sigma value from 2.30 to 2.36 indicates a significant improvement in product quality.